2002
DOI: 10.1046/j.1365-2362.2002.0320s1050.x
|View full text |Cite
|
Sign up to set email alerts
|

Nature of nontransferrin‐bound iron

Abstract: Nontransferrin-bound iron is now recognized to exist by many workers. It is present in the serum of patients suffering from a wide range of disease states and may be induced by certain therapeutic treatments. The chemical nature of this iron pool is unknown but almost certainly it is a multicomponent pool including a considerable proportion of protein-bound iron.Methods are required to separate and quantify these different components. The biological properties of the individual isoforms need to be established;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 46 publications
(52 reference statements)
0
81
0
2
Order By: Relevance
“…This contrasts with the fact that, in thalassemic patients, most of the plasma NTBI is excluded by size filtration 1,12 and that its chemical determination requires harsh extraction measures. [10][11][12] This would indicate that in thalassemic plasma in general and, as we found in this study, in plasma from non-chelated patients, the chemically active forms of NTBI consist of high-molecular weight complexes which may be protein-associated. We predict that for macromolecular forms to gain access to cells, they would need to be initially transferred as fluid cargo or membrane adsorbed species that are taken up by endocytosis and subsequently by transmembrane mechanisms into the cytosol.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…This contrasts with the fact that, in thalassemic patients, most of the plasma NTBI is excluded by size filtration 1,12 and that its chemical determination requires harsh extraction measures. [10][11][12] This would indicate that in thalassemic plasma in general and, as we found in this study, in plasma from non-chelated patients, the chemically active forms of NTBI consist of high-molecular weight complexes which may be protein-associated. We predict that for macromolecular forms to gain access to cells, they would need to be initially transferred as fluid cargo or membrane adsorbed species that are taken up by endocytosis and subsequently by transmembrane mechanisms into the cytosol.…”
Section: Introductionmentioning
confidence: 52%
“…13,20 The probe undergoes swift and stoichiometric quenching by interacting with labile iron and recovers its fluorescence when challenged with iron chelators. Using CALG-laden RAW macrophages and fluorescence microscopy live imaging, we found that ferric compounds such as ferric citrate, considered a major component of NTBI in iron overloaded sera, 11,12 failed to evoke changes in cytosol fluorescence over a period of 90 min, unless the medium was supplemented with human serum albumin (HSA) ( Figure 1 shows data for only two time points: 0 and 40 min).…”
Section: Ntbi Uptake Into Cells As Revealed With Cytosolic Iron Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased presence of free iron pool will enhance oxidant generation leading damage to biomolecules. However, at present the exact nature of free iron pool in vivo is not clearly known (23), it needs further studies in this population with various study designs to know the catalytic action of free iron and its relation to glucose. …”
Section: Resultsmentioning
confidence: 99%
“…Another aspect is that iron is almost a one way element and only few physiological avenues for its removal from human organism are known to exist. There is a lacunae in the literature regarding the precise way of removal and the shelf life of NTBI, though some studies state its clearance from highly vascular organs like liver and heart [1]. Even after lapse of 34 years of its first mentioning of NTBI by Hershko et al [2] the equivocal of definition of NTBI is difficult proposition due its heterogeneous nature.…”
Section: Introductionmentioning
confidence: 99%